The Implementation of The Teachers’ Development Program in San Isidro Labrador Elementary School - Michelle Mae B. Agohayon; Ardrian D. Malangen. Maed (Research Parks Publishing LLC, 2023)
The landscape of public education continues to shift and accountability requirements continue to mount, educational leaders' primary concern is the training and development of successful teachers. A critical component of this development is equipping teachers with the tools essential for success through professional development. Moreover, the purpose of the study is to determine the implementation of the teachers’ development program in San Isidro Elementary School in terms of Needs Assessment, Content, Strategy Delivery, Monitoring and Evaluation. The study utilized descriptive correlational design and used survey questionnaire as the main data-gathering instrument, which was administered to 90 teachers. The results revealed that the assessment of the respondents the teachers’ development program was successfully implemented, the challenges encountered in the implementation of the teachers’ development program are sometimes experience and no significant differences in the respondents’ assessment when grouped according to age, sex, years in service, and teaching position, but significantly different in terms of educational attainment. Thus, nurture and support an effective reward and incentive system that can improve accountability, encourage personal development, strengthen continuous learning, and motivate teacher participation. The school's training and development group should concentrate on issues that address the needs and weaknesses of teachers (educational attainment).